School Crises and Methods 0f Dealing with Them as Conceived by High School Principals in Kuwait - Sameera M. AbdulWahab; Mohammed R. Al Mursy (Sultan Qaboos University, 2014)
The current study aimed to identify the crises at high schools in Kuwait and the methods of managing them as perceived by principals (males, females) of high schools in Kuwait. The sample for the study consisted of randomly-chosen 85 principals, representing 70% 0f the total sample of study covering the six educational districts in Kuwait. The results showed significant differences at 0.001 for crises determining at female schools, at 0.05 for the crises between districts at Ahmady and Hawally educational districts, and at 0.02 for obstacles to school crises management at female schools; but no significant differences for these obstacles according to educational districts, and no differences were found for crises management requirements according to the gender or the educational districts.